Contemporary State of Resource Potential of Agriculture in South Russia - Trukhachev, Vladimir Ivanovich; Sklyarov, Igor Yurevich; Sklyarova, Julia Mikhailovna; Latysheva, Lyudmila Anatolevna; Lapina, Helena Nikolayevna (International Journal of Economics and Financial Issues, 2016)
The present article estimates the resource potential of the agriculture, and reveals basic factors affecting agricultural production and agrarian market in the region. The author defines the reserves related to increasing the economic efficiency of the AIC subjects. It determines multiplicative change and reveals the factors that affect the stability and efficiency of the development of the organizational and economic mechanism of the agricultural business. The research of the resource potential of the Stavropol Territory proves high potential of the region’s agricultural business development. The work specifies that there is a stable tendency of the increase in the efficiency of the agricultural production. The author makes the conclusion that subject to support of state structures it is necessary to create conditions for the agricultural business, stimulate the implementation of intensive power saving technologies, reduce the deficit of productive capacities to store and process agricultural products, ensure the inflow of qualified personnel in organizations of the AIC, make financial resources more accessible, increase the volumes of the financial support for large, medium- and small-sized agricultural organizations, and create a long-term program of implementing the intervention program on the agrarian market. Keywords: agricultural business, resources, labor, land, innovations, investment activity, JEL Classifications: J43, E22, N54